Neuroinflammation in neurodegeneration via microbial infections - Tran, Van Thi Ai; Lee, Luke P.; Cho, Hansang (Frontiers in Immunology, 2022)
Recent epidemiological studies show a noticeable correlation between chronic microbial infections and neurological disorders. However, the underlying mechanisms are still not clear due to the biological complexity of multicellular and multiorgan interactions upon microbial infections. In this review, we show the infection leading to neurodegeneration mediated by multiorgan interconnections and neuroinflammation. Firstly, we highlight three inter-organ communications as possible routes from infection sites to the brain: nose-brain axis, lung-brain axis, and gut-brain axis. Next, we described the biological crosstalk between microglia and astrocytes upon pathogenic infection. Finally, our study indicates how neuroinflammation is a critical player in pathogen-mediated neurodegeneration. Taken together, we envision that antibiotics targeting neuro-pathogens could be a potential therapeutic strategy for neurodegeneration.